PENGEMBANGAN SISTEM IDENTITAS PRODUK SEBAGAI STRATEGI PENGUATAN BRAND PADA UMKM FAITH-BASED LIFESTYLE - Andreas Rio Adriyanto; Maria Josef Retno Budi Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2026)
Exsultate! is a faith-based lifestyle brand that produces Catholic-themed apparel as a medium for expressing faith through fashion. This community service project was a continuation of a previous program that had successfully redesigned the brand identity, developed informative hangtags, and created liturgical-themed T-shirt designs. However, several challenges remained, including the absence of an integrated packaging system, internal garment labels, a limited range of design content, and an inefficient production strategy for a start-up SME. The program aimed to strengthen the product system through the design of packaging, internal labels, visual content, and a printed product catalog as appropriate design-based technologies to enhance the competitiveness of the enterprise. The project employed a combination of participatory design and design thinking through the stages of discovery, creation, refinement, implementation, and production, actively involving the partner throughout the process. The outcomes included twelve new design concepts, increasing the product collection to sixteen designs, DTF-based internal garment labels, a packaging system that reinforced the brand identity, and a printed catalog as a marketing and sales medium. In addition, a lean production strategy was implemented through a display sample, print-on-demand, and pull system approach, reducing inventory risk while improving cash flow efficiency. The program successfully strengthened Exsultate!'s brand identity and enhanced the partner's capacity in branding, product development, and sustainable production management.